War and media : the emergence of diffused war - Hoskins, Andrew, 1967-; O'Loughlin, Ben, 1976- (Polity, 2010)
The trinity of government, military and publics has been drawn together into immediate and unpredictable relationships in a "new media ecology" that has ushered in new asymmetries in the waging of war and terror. To help us understand these new relationships, Andrew Hoskins and Ben O'Loughlin here provide a timely, comprehensive and highly readable survey of the field of war and media. War is diffused through a complex mesh of our everyday media. Paradoxically, this both facilitates and contains the presence and power of enemies near and far. The conventions of so-called traditional warfare have been splintered by the availability and connectivity of the principal locus of war today: the electronic and digital media. Hoskins and O'Loughlin identify and illuminate the conditions of what they term "diffused war" and the new challenges it raises for the actors who wage and counter warfare, for their agents and mechanisms of the new media and for mass publics. This book offers an invaluable review of the key literature and presents a fresh approach to the understanding of the dynamic relationships between war and media. It will be welcomed by a broad range of students taking courses on war and media and related modules, especially in media, communication and cultural studies, politics and international relations, sociology, journalism, and security studies. -- Publisher description.